2007
DOI: 10.1002/asi.20744
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variations in the aging of scientific literature: From exponential growth to steady‐state science (1900–2004)

Abstract: Despite a very large number of studies on the aging and obsolescence of scientific literature, no study has yet measured, over a very long time period, the changes in the rates at which scientific literature becomes obsolete. This article studies the evolution of the aging phenomenon and, in particular, how the age of cited literature has changed over more than 100 years of scientific activity. It shows that the average and median ages of cited literature have undergone several changes over the period. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 22 publications
8
112
0
8
Order By: Relevance
“…The decreasing mean of the time to peak indicates that in recent times papers are taking less time to reach the peak of their attention. This result seems to be consistent with previous findings (Egghe, 2010;Larivière et al, 2008) showing, both theoretically and empirically, that the average reference age is an increasing function of time. This would suggest that more recent papers are able to dig deeper in scientific literature, reducing the amount of attention available for papers published in recent years and therefore causing a shortening of the time needed to peak.…”
Section: Evolution Of the Time To Peaksupporting
confidence: 93%
“…The decreasing mean of the time to peak indicates that in recent times papers are taking less time to reach the peak of their attention. This result seems to be consistent with previous findings (Egghe, 2010;Larivière et al, 2008) showing, both theoretically and empirically, that the average reference age is an increasing function of time. This would suggest that more recent papers are able to dig deeper in scientific literature, reducing the amount of attention available for papers published in recent years and therefore causing a shortening of the time needed to peak.…”
Section: Evolution Of the Time To Peaksupporting
confidence: 93%
“…JIFs can avoid citing article publication delays if it is accepted that the average impact of a journal is an appropriate proxy for the impact of its articles (but see: Lozano, Larivière, & Gingras, 2012; and note also the time dimension: Larivière, Archambault, & Gingras, 2008) 1 Thelwall, M. (in press). Are Mendeley reader counts high enough for research evaluations when articles are published?…”
Section: Introductionmentioning
confidence: 99%
“…In the past, this was stable at ten references per paper (Price 1963), but it is widely assumed this number has since increased. Larivière et al (2008) have shown that while the growth of publications in medical fields and in natural sciences & engineering is progressively slowing down since 1980 the number of references has not leveled off, which would indicate a growth in the number of references per paper. A paper that itself contains many references to previous work is likely to develop a stronger standing than a paper with no or few references (Latour 1987;Latour and Woolgar 1986).…”
Section: Introductionmentioning
confidence: 99%